THE INTENTION TO INVEST IN SUKUK: DO VALUE PROPOSITIONS MATTER? - Pepadri, Isman; Hidayah, Nur (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the level of importance-performance and influence of value proposition indicators on investment decisions in Retail Sukuk by integrating two analytical frameworks. The first is the Importance-Performance Analysis assessed through descriptive statistics, and the second is the Theory of Planned Behavior, tested using inferential statistical analysis. Based on responses from 152 deposit holders residing in Jakarta, the findings revealed that four indicators shaping behavioral attitudes significantly influenced investment intentions. Among these, state guarantees and competitive coupon rates must be maintained as core value propositions; support for government programs shows potential to become a key value; and the fixed coupon rate does not require emphasis. Additionally, the four indicators influencing perceived behavioral control also had a positive effect on intention. Affordable investment thresholds and ease of access to purchasing must be sustained as key strengths; short tenor does not necessitate enhancement; and information regarding issuance should become a primary area for improvement. Practically, these findings suggest that issuers must improve their communication strategies and explore opportunities to offer more competitive coupon rates for Retail Sukuk. Theoretically, the combination framework proves to be a relevant and effective approach, yielding valuable empirical insights for researchers.